Solvent-free atom transfer radical polymerization for the preparation of poly(poly(ethyleneglycol) monomethacrylate)-grafted Fe3O4 nanoparticles: Synthesis, characterization and cellular uptake - Fan, Q.-L. (2014)
10.1016/j.biomaterials.2007.08.039